A short note on physical properties to irradiated nuclear fuel by means of X-ray diffraction and neutron scattering techniques - Abdullah Y.; Husain H.; Hak C.R.C.; Alias N.H.; Yusof M.R.; Kasim N.A.; Zali N.M.; Mohamed A.A. (American Institute of Physics Inc., 2023)
For nuclear reactor applications, understanding the evolution of the fuel materials microstructure during irradiation are of great importance. This paper reviews the physical properties of irradiated nuclear fuel analysis which are considered to be of most importance in determining the performance behavior of fuel. X-rays diffraction was recognize as important tool to investigate the phase identification while neutron scattering analyses the interaction between uranium and other materials and also investigation of the defect structure. 2015 AIP Publishing LLC.